Once bitten twice shy? E xperience managing violent conflict risk and MNC subsidiary‐level investment and expansion - Oh, Chang Hoon; Oetzel, Jennifer (Strategic Management Journal, 2017)
Research summary : Researchers have increasingly emphasized the need to better understand how context affects the value of experiential learning. We address this gap by investigating when corporate‐level experience can be leveraged across borders and when experience needs to be country‐specific to be valuable. We test our hypotheses using a unique multi‐source panel dataset of 379 large MNCs from 29 home countries and their subsidiaries in 117 host countries over a 10‐year period, 1999–2008. In contrast to prior research, we find that the ability of a firm to leverage its experience with political risk across borders is limited by the type of risk involved. Experience with nonstate violent conflicts may be transferrable, but only country‐specific experience appears to yield measureable benefits for conflicts involving the host country government . Managerial summary : Violent conflicts not only increase social unrest but also impose added costs of doing business. For managers who find themselves in the midst of violent conflicts or who wish to survive and potentially gain a competitive advantage in operating in such challenging environments, is it possible to learn to manage such a seemingly “unmanageable” problem? In contrast to studies that have examined other types of political risk, we find that the ability of a firm to leverage its experience with violent conflict risk across borders is limited. Specifically, only country‐specific experiential knowledge about how the host government prepares and manages such conflict risks yields measureable economic benefits for MNCs and their subsidiaries operating in countries during conflict . Copyright © 2016 John Wiley & Sons, Ltd.